2019
DOI: 10.2196/preprints.14989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conversational Agents for Chronic Disease Self-Management: A Systematic Review (Preprint)

Abstract: BACKGROUND Conversational agents have the potential to deliver patient-centered interventions that focus on goal setting, feedback, and education. However, little is known how these agents may be utilized to assist patients with chronic disease self-management. OBJECTIVE The objective of this study was to systematically review the literature to assess how conversational agents have been used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In the last decade, CAs’ popularity has increased, particularly those that use unconstrained natural language [ 3 , 4 , 5 ]. For example, consumers can talk to CAs on their smartphones for daily tasks, such as managing their calendars and retrieving information [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, CAs’ popularity has increased, particularly those that use unconstrained natural language [ 3 , 4 , 5 ]. For example, consumers can talk to CAs on their smartphones for daily tasks, such as managing their calendars and retrieving information [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, CAs can play an useful role in health care, improving consultations by assisting clinicians and patients, supporting consumers with behavior change, and assisting older people in their living environments [ 13 , 14 , 15 ]. They can also help in completing specific tasks such as self-monitoring and overcoming obstacles for self-management, which is important in chronic disease management and in the fight against pandemics [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies with conversational agents, especially when they have a physical embodiment or are computationally heavy, still take place in the controlled settings of a lab (Griffin et al, 2020;. Such evaluations in controlled conditions provide valuable information and should be performed during development, for example, to investigate relations between personalisation of conversational agents and user experience (Kocaballi et al, 2019).…”
Section: Evaluation Of Tailored Contentmentioning
confidence: 99%
“…They also reported that agents often had to ask questions more than once to be able to process the response. In addition to interpretation challenges, free text input also raises concerns with respect to privacy and safety (Griffin et al, 2020;Tudor Car et al, 2020). In contrast, it is argued that speech input might make applications more accessible and intuitive (Dingler et al, 2021), for example, for those who have difficulty reading or typing (Tudor Car et al, 2020).…”
Section: Input and Output Modalitiesmentioning
confidence: 99%